Blood staining of the posterior capsule caused by Terson syndrome. Issue 2 (April 2019) - Hanai, Kaori; Hashimoto, Masato; Sasaki, Masako; Nakamura, Hirohiko
Abstract : N/A: A 49‐year‐old man noticed bilateral acute visual loss after a subarachnoid hemorrhage caused by right vertebral artery dissection. Ophthalmologic findings were consistent with a diagnosis of Terson syndrome. A 25‐gauge pars plana vitrectomy was performed after phacoemulsification with intraocular lens implantation; all procedures were uneventful. However, the operative field was very hazy. A small transparent circle, presumably the basement of Cloquet canal, was observed in the center of the cloudy operative field. We concluded that the posterior capsule had been stained by the vitreous hemorrhage. Therefore, a posterior capsulotomy was performed around the small circle, resulting in a clear operative field, and the surgery proceeded safely.